Pengaruh Pemberian Ekstrak Biji Petai (Parkia speciosa) Terhadap Gambaran Histopatologi Ginjal Bagian Tubulus Proksimal Pada Tikus Putih (Rattus norvegicus) Jantan Galur Wistar yang diinduksi Paracetamol - AVINDA DEVIANA (HANG TUAH MEDICAL JOURNAL, 2018)
Abstract Background.Paracetamol, which is one of the NSAIDs (Non Steroidal Anti Inflammatory Drugs) is widely used by the wider community as a therapeutic and pain-reducing therapy. In addition to its many uses, paracetamol can cause a variety of serious toxicities, including nephrotoxicity. Bitter bean extract (Parkia speciosa) has a flavonoid compound which is an antioxidant. Methods.This was a laboratory experimental study with post-test only controlgroup design using 24 rats divided into 3 groups. Positive control group fed with standard diet, aquades and bitter bean extract (Parkia speciosa); each rat in the treatment group 1 was induced with paracetamol 9 mg / day orally; and each rat in the treatment group 2 was given bitter bean extract (Parkia speciosa) 7,2 mg / day induced paracetamol 9 mg / day after 45 min. The kidneys were taken by surgery on the 15th day and microscopically examined. The data were analyzed using IBM SPSS version 23 with Kruskal-Wallis method. Result. Data analysis using Mann Whitney test showed significant difference between positive control group and treatment 1 p = 0.000 (p <0,05). Also in comparison between the positive control group and the treatment group 2 showed a significant difference p = 0.001 (p <0.05). However, there was no significant difference between treatment group 1 and treatment group 2 p = 0,678 (p> 0,05). Conclusion. The administration of grain seed extract (Parkia speciosa) did not decrease paracetamol-induced kidney damage